2013
DOI: 10.1093/nar/gkt574
|View full text |Cite
|
Sign up to set email alerts
|

DNA motif elucidation using belief propagation

Abstract: Protein-binding microarray (PBM) is a high-throughout platform that can measure the DNA-binding preference of a protein in a comprehensive and unbiased manner. A typical PBM experiment can measure binding signal intensities of a protein to all the possible DNA k-mers (k = 8 ∼10); such comprehensive binding affinity data usually need to be reduced and represented as motif models before they can be further analyzed and applied. Since proteins can often bind to DNA in multiple modes, one of the major challenges i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
48
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
5
3

Relationship

3
5

Authors

Journals

citations
Cited by 60 publications
(57 citation statements)
references
References 71 publications
2
48
0
Order By: Relevance
“…The performance of the models is quite satisfactory since the mode of Spearman rank correlation coefficient is near 0.9. On the other hand, it can be observed that the model lengths are usually around 12 ∼ 14 nt which are consistent with the existing TFBS knowledge [20]. Each dot denotes a single method's performance on a single dataset.…”
Section: Model Analysissupporting
confidence: 81%
See 2 more Smart Citations
“…The performance of the models is quite satisfactory since the mode of Spearman rank correlation coefficient is near 0.9. On the other hand, it can be observed that the model lengths are usually around 12 ∼ 14 nt which are consistent with the existing TFBS knowledge [20]. Each dot denotes a single method's performance on a single dataset.…”
Section: Model Analysissupporting
confidence: 81%
“…Robust estimate procedures proposed in RankMotif++ [14] can then be applied to learn the positive k-mers. Nonetheless, it has been pointed out that such a robust procedure may not be suitable for all proteins [20]. In light of that, the highly ranked k-mers are regarded as the positive k-mers in this study.…”
Section: Problem Descriptionmentioning
confidence: 99%
See 1 more Smart Citation
“…For the repeats larger than the read length, the current tools can easily capture them by assembling from NGS reads, whereas for those smaller than the read length, such as motifs, the assembly-based tools are useless. Consequently, for capturing short repeats, a motif identification-based method, such as kmerHMM (Wong et al, 2013), will be more helpful than the assembly-based method.…”
Section: Discussionmentioning
confidence: 99%
“…Robust estimate procedures proposed in RankMotif++ [16] can then be applied to learn the positive k-mers. Nonetheless, it has been pointed out that such a robust procedure may not be suitable for all proteins [21]. In light of that, the highly ranked k-mers are regarded as the positive k-mers in this paper.…”
Section: Problem Descriptionmentioning
confidence: 99%